Influence of water content of surrounding soil on surface strength of cement-treated soil - YOSHIDA, Masahiko; NAKARAI, Kenichiro; KIYOTA, Masato; IZUO, Hidefumi (Japanese Geotechnical Journal, 2019)
Cement-treated soil specimens were contacted with surrounding soils having different water contents in order to investigate surface strengths affected by calcium leaching. The strength of sound parts of the treated-soils continuously increased until 2 years, the maximum material age in this study. On the other hand, the surface layer of the treated-soils showed lower strength development by contact with the surrounding soils. At the interface between the treated and surrounding soils, the alteration caused by calcium leaching was observed. The altered depth by calcium leaching varied depending on the water contents of the surrounding soils. The lower the water contents of the surrounding soils, the smaller the calcium decreased depth of the treated-soil. However, the relationships between the calcium decrease ratio and the strength decrease ratio of the treated soil showed similar trends regardless of the water contents of the surrounding soils. The higher leaching resistance of the treated soil contacted with the low water content soil could be explained by increase in solid ration at the surface layer, due to transfer of water from the treated soil to the surrounding soil before hardening of the treated soil.